An Existentialism Approach in Language and Literature Education to Build Student Personality - Arwan, Arwan; Suastra, Wayan; Atmaja, Ananta Wikrama Tungga; Tika, I Nyoman (JUPE : Jurnal Pendidikan Mandala, 2024)
This study aims to explore the application of the philosophy of existentialism approach in learning the Indonesian language and literature among students of the Indonesian Language and Literature Education Study Program at STKIP Harapan Bima. The problem being studied is the extent to which the existentialist approach can improve students' understanding of literary works and its impact on the development of students' critical and reflective thinking skills. This study uses a qualitative approach with a case study method, where data is collected through observation, in-depth interviews, and document analysis. The data analysis technique used is thematic analysis, which aims to identify the main themes that emerge from the research results. The study results show that applying the existentialism approach in learning the Indonesian language and literature can increase students' involvement in the learning process, deepen their understanding of literary works, and strengthen their ability to reflect and criticize the values contained in literature. Students also better understand existentialism themes such as freedom, responsibility, and the search for meaning in life. Overall, this research contributes to the development of an Indonesian language and literature curriculum that is more meaningful and relevant to students' lives, as well as opening up opportunities for further research in this field.